Is Hearing Impairment Causally Associated With Falls? Evidence From a Two-Sample Mendelian Randomization Study - Wang, Jun; Liu, Dan; Tian, E.; Guo, Zhao-Qi; Chen, Jing-Yu; Kong, Wei-Jia; Zhang, Su-Lin (Frontiers in Neurology, 2022)
Background: Observational studies have suggested that hearing impairment (HI) was associated the risk of falls, but it remains unclear if this association is of causal nature. Methods： A two-sample Mendelian randomization (MR) study was conducted to investigate the causal association between HI and falls in individuals of European descent. Summary data on association of single nucleotide polymorphisms (SNPs) with HI were obtained from the hitherto largest genome-wide association study (GWAS) (n=323,978), and statistics on association of SNPs with falls were extracted from another recently published GWAS (n=461,725). MR Steiger filtering method was applied to determine the causal direction between HI and falls. Inverse variance weighted (IVW) method was employed as the main approach to analyze the causal association between HI and falls, while weighted median, simple mode, weighted mode and MR-egger methods were used as complementary analyses. MR-Egger intercept test, MR-PRESSO test and Cochran’s Q statistic were performed to detect the potential directional pleiotropy and heterogeneity, respectively. The odds ratio (OR) with 95% confidence intervals (CIs) was used to evaluate this association. Results: A total of 18 SNPs were identified as valid instrumental variables in our two-sample MR analysis. The positive causality between HI and risk of falls was indicated by IVW [OR 1.108 (95% CI 1.028, 1.194), P = 0.007]. The sensitivity analyses yielded comparable results. The ‘‘leave-one-out” analysis proved that lack of a single SNP did not affect the robustness of our results. The MR-Egger intercept test exhibited that genetic pleiotropy did not bias the results [intercept = -2.4E-04, SE = 0.001, P = 0.832]. Cochran’s Q test revealed no heterogeneity. Conclusions: Our MR study revealed a causal association between genetically-predicted HI and falls. These results provide further evidence supporting the need to effectively manage HI to minimize fall risks and improve quality of life.